Realization and Encompassment of Torque and Speed Pulsations Depriciation in Permanent Magnet Synchronous Motor Employing ILC-Sine PWM - Subha Lakshmi, N.; Allirani, S. (International Journal of Engineering and Technology, 2018)
The rotor of PMSM is made of permanent magnet and thus it does not rely on an external source to generate the rotor flux. The major drawback of Permanent Magnet Synchronous Motor is torque ripple, where speed oscillations are generated and weaken the function of drive which operates at low speed. This paper propose the Iterative Learning Controller (ILC) with SPWM to extinguish the speed and torque ripple in PMSM driven by field oriented control. The reference motor speed is compared with actual motor speed by the speed controller, and generates the reference current iqref value where the speed error is reduced. Depending on iqref value SPWM pulses are generated. These generated pulses are sent to the three phase inverter. The major merit and effeciency of the proposed method for speed ripple and torque suppression are designed, analysed, simulated and implemented in hardware using TMS320F2812. The outcomes obtained show the significant minimisation of speed ripples using PI plugged in ILC with SPWM. Thus reduction of speed ripple is done by this proposed method.Â Â